1988
DOI: 10.1103/physrevlett.60.1703
|View full text |Cite
|
Sign up to set email alerts
|

High proton momenta and nucleon-nucleon correlations in the reaction3He(e,e’p)

Abstract: Electron-scattering cross sections for the reaction 3 He(e,e'p) have been measured for recoil momenta between 300 and 600 MeV/c and for missing energies up to 90 MeV. Proton momentum distributions in 3 He, corrected for final-state-interaction and meson-exchange effects, have been obtained from 318 to 600 MeV/c for the pd channel and from 290 to 515 MeV/c for the ppn channel. Explicit evidence for nucleon-nucleon correlations is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(39 citation statements)
references
References 16 publications
2
37
0
Order By: Relevance
“…Experimental momentum distributions for the transitions to the ground state and first excited state of 6 He have been measured via the reaction 7 Li(e, e ′ p) 6 He, in the missing momentum range from -70 to 260 MeV/c. They are compared to theoretical distributions calculated with mean-field wave functions and with variational Monte Carlo (VMC) wave functions which include strong state-dependent correlations in both 7 Li and 6 He. These VMC calculations provide a parameter-free prediction of the momentum distribution that reproduces the measured data, including its normalization.…”
mentioning
confidence: 99%
“…Experimental momentum distributions for the transitions to the ground state and first excited state of 6 He have been measured via the reaction 7 Li(e, e ′ p) 6 He, in the missing momentum range from -70 to 260 MeV/c. They are compared to theoretical distributions calculated with mean-field wave functions and with variational Monte Carlo (VMC) wave functions which include strong state-dependent correlations in both 7 Li and 6 He. These VMC calculations provide a parameter-free prediction of the momentum distribution that reproduces the measured data, including its normalization.…”
mentioning
confidence: 99%
“…Measurements for performed at Saclay (141,147) have shown that for large momenta there is a prominent peak in the missing-energy distribution whose centroid is consistent with this quasideuteron mechanism and that the momentum distribution for is similar to that of the deuteron. One member of the pair is detected in the experiment while the undetected spectator carries away a large kinetic energy, thereby representing a large excitation energy with respect to the ground state of the A -1 system.…”
Section: Continuum Contributionsmentioning
confidence: 93%
“…In fact, Kohno 19 pointed out that the mesonic contribution could change the ratio R G by as much as 10% for I2 C. Evidence for nucleon-nucleon correlations was presented in a study of the 3 HeO,ep) reaction. 24 Further calculations are needed to get insight into the role of these two effects for the 6 Li(e,e'p) reaction.…”
Section: Quasielastic Electron Scattering Is Assumed To Be Dominated mentioning
confidence: 99%